Tribological properties of MoS2 coating for ultra-long wear-life and low coefficient of friction combined with additive g-C3N4 in air - Yupeng Zhang; Panpan Li; Li Ji; Xiaohong Liu; Hongqi Wan; Lei Chen; Hongxuan Li; Zhiliang Jin (Friction)
Abstract The solid lubricant MoS2 demonstrates excellent lubricating properties, but it spontaneously oxidizes and absorbs moisture in air, and thus results in poor wear resistance and short wear-life. In this study, the additive g-C3N4 (CN) was successfully combined with MoS2 via hydrothermal synthesis as a solid lubricant for the first time. Meanwhile, a low friction coefficient (COF, μ = 0.031) and ultra-long wear-life of CN/MoS2 compared to pure MoS2 in air were demonstrated. The functional groups and good crystallinity of the lubricant material were characterized via Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). The formed valence states in CN/MoS2 were analyzed via X-ray photoelectron spectroscopy (XPS). The characterized results of the scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM) show the morphology and interior crystal phase structure of CN/MoS2. From the cross-section analysis, the presence of iron oxide nanoparticles lubricating film is synergistic with CN/MoS2 film during the friction process, resulting in its ultra-long wear-life. In particular, the friction mechanism of interlayer sliding friction combined with energy storage friction was analyzed and proposed.